KAJIAN PENGARUH CAMPURAN ASPHALT DENGAN TAMBAHAN BENZOIN TERHADAP KARAKTERISTIK MARSHALL - Kartika Indah Sari; Rizky Franchitika; Asri Afriliany Surbakti; Nurkhasanah Rina Puspita; Soraya Muthma Innah Nasution (Bajang Institute, 2025)
Factors that support the development of an area are improving transportation facilities in the form of roads. The aim of improving roads is to facilitate all activities directly related to movement, both people and goods. For this reason, improving the quality of transportation facilities in the form of roads currently needs attention. Efforts to improve road quality can be carried out by research in the form of variations in pavement layer mixtures with various kinds of added materials. One variation of the mixture that can be used is benzoin (incense resin). Benzoin is a forest product that has similar physical properties to asphalt. With this research, it is hoped that the addition of benzoin will affect the results of the Asphalt Concrete-Binder Course mixture when viewed from the Marshall characteristics. This research method uses the Marshall Method and the Marshall test procedure follows SNI 06-2489-1991 with reference to the 2018 General Specifications. The research results show that the optimum asphalt content obtained for each variation is: Normal Asphalt (5.55%), Asphalt with 5% benzoin added (5.45%), Asphalt with 10% benzoin added (5.35%) and Asphalt with 15% benzoin added (5.25%). Next, test values were obtained after optimum asphalt content for all parameters, namely stability, flow, VIM, VMA, VFB, Marshall Quotient and residual stability values for all variations. And the final research results, that the use of 15% benzoin additives in asphalt mixtures cannot be used because the Marshall residual stability value does not meet the 2018 General Specifications.